Wintering Areas and Recovery Rates of Brünnich’s Guillemots Uria lomvia Ringed in the Svalbard Archipelago - Bakken, Vidar; Mehlum, Fridtjof (ARCTIC, 2010)
We mapped wintering areas and estimated the recovery rates of Brünnich’s guillemots (thick-billed murres) ringed in Svalbard during 1954–98. Recoveries were reported from Iceland, Greenland, and Newfoundland. An intensive hunt occurs annually off Greenland and Newfoundland, and more than 95% of the recovered birds were reported as shot. Birds recovered as immatures differed from birds recovered as adults in their temporal and spatial distribution. Immatures were more exposed to hunting because they arrived at the hunting areas earlier in the autumn and formed a higher proportion of the population in hunting areas farthest away from Svalbard. The recovery rate of birds ringed in Svalbard as chicks was comparable to the recovery rate reported from Canada. Interestingly, no Svalbard birds have ever been recovered in the southern part of the Barents Sea or along the Norwegian coast, suggesting that these areas are not important to the Svalbard population. The distribution of winter recoveries of birds ringed in Svalbard was compared to the winter recovery areas of Brünnich’s guillemots ringed elsewhere in the North Atlantic. Only birds ringed in Svalbard have been recovered in Iceland in winter. On a cartographié les aires d’hivernage des guillemots de Brünnich (marmettes de Brünnich) bagués au Svalbard de 1954 à 1998, et estimé leurs taux de recapture. Des recaptures ont été signalées en Islande, au Groenland et à Terre-Neuve. Durant la chasse intensive qui a lieu chaque année au large du Groenland et de Terre-Neuve, 95 % des oiseaux recapturés auraient été abattus au fusil. Les oiseaux recapturés en tant qu’immatures différaient dans leur distribution temporelle et spatiale de ceux recapturés en tant qu’adultes. Les immatures étaient plus exposés à la chasse parce qu’ils arrivaient dans les zones de chasse plus tôt à l’automne et qu’ils formaient une plus grande proportion de la population dans les zones de chasse les plus éloignées du Svalbard. Le taux de recapture des oiseaux bagués au Svalbard en tant ...